Creation of Al‐Enriched Mesoporous ZSM‐5 Nanoboxes with High Catalytic Activity: Converting Tetrahedral Extra‐Framework Al into Framework Sites by Post Treatment. (26th March 2020) - Jiao, Yilai; Forster, Luke; Xu, Shaojun; Chen, Huanhao; Han, Jingfeng; Liu, Xuqing; Zhou, Yangtao; Liu, Jinmin; Zhang, Jinsong; Yu, Jihong; D'Agostino, Carmine; Fan, Xiaolei
Abstract: ZSM‐5 zeolite nanoboxes with accessible meso ‐micro‐pore architecture and strong acid sites are important in relevant heterogeneous catalysis suffering from mass transfer limitations and weak acidities. Rational design of parent zeolites with concentrated and non‐protective coordination of Al species can facilitate post‐synthetic treatment to produce mesoporous ZSM‐5 nanoboxes. In this work, a simple and effective method was developed to convert parent MFI zeolites with tetrahedral extra‐framework Al into Al‐enriched mesoporous ZSM‐5 nanoboxes with low silicon‐to‐aluminium ratios of ≈16. The parent MFI zeolite was prepared by rapid ageing of the zeolite sol gel synthesis mixture. The accessibility to the meso ‐micro‐porous intra‐crystalline network was probed systematically by comparative pulsed field gradient nuclear magnetic resonance diffusion measurements, which, together with the strong acidity of nanoboxes, provided superb catalytic activity and longevity in hydrocarbon cracking for propylene production. Abstract : ZSM‐5 nanoboxes with low SARs : Rapid ageing of a sol gel synthesis mixture produces a parent zeolite with tetrahedral extra framework Al and a low silicon‐to‐aluminium ratio (SAR) value of ≈12, which is transformed to mesoporous ZSM‐5 nanoboxes with low SARs of ≈16 during post‐synthetic TPAOH treatment. The mesoporous ZSM‐5 nanoboxes show comparatively enhanced mass transfer ability, catalytic cracking activity and longevity.